Contemporary Approach in Muhammad Syahrur's Thought on Islamic Law - Azwarfajri, Azwarfajri; HM Yasin, Taslim; Hakim, Lukman (Program Studi Aqidah dan Filsafat Islam, 2024)
Contemporary Islamic thought is marked by an awareness of the coexistence of tradition (turath) on one side and modernity (hadathah) on the other. Syahrur introduces a new approach that emphasizes rationality and contextuality in understanding religious texts, especially in the field of Islamic law. This study aims to analyze the construction of Syahrur’s thought through methods of defamiliarization, rejection of synonymity, and the hudud (limits) theory as an effort to renew Quranic understanding in line with contemporary contexts. The research method used is a literature study with a qualitative descriptive approach, examining various concepts and Syahrur’s critiques of contemporary Islamic thought. The results indicate that Syahrur offers a flexible Quranic interpretation method, rejects classical literature, prioritizes an objective-positivistic approach, and employs mathematical principles to interpret law in a flexible manner. Syahrur believes that the Quran is sufficient as the primary source of law without reliance on the Sunnah. Although his views are controversial and opposed by traditional scholars, Syahrur is confident that his approach opens opportunities for Islamic legal reform relevant to the demands of the times.